Appropriateness of endoscopic surveillance recommendations in organised colorectal cancer screening programmes based on the faecal immunochemical test. Issue 11 (21st August 2015) - Zorzi, Manuel; Senore, Carlo; Turrin, Anna; Mantellini, Paola; Visioli, Carmen Beatriz; Naldoni, Carlo; Sassoli de' Bianchi, Priscilla; Fedato, Chiara; Anghinoni, Emanuela; Zappa, Marco; Hassan, Cesare; ,
Abstract : Objectives: To assess the appropriateness of recommendations for endoscopic surveillance in organised colorectal cancer (CRC) screening programmes based on the faecal immunochemical test (FIT). Design: 74 Italian CRC screening programmes provided aggregated data on the recommendations given after FIT-positive colonoscopies in 2011 and 2013. Index colonoscopies were divided into negative/no adenoma and low- risk, intermediate-risk and high-risk adenomas. Postcolonoscopy recommendations included a return to screening (FIT after 2 years or 5 years), an endoscopic surveillance after 6 months or after 1 year, 3 years or 5 years, surgery or other. We assessed the deviation from the postcolonoscopy recommendations of the European Guidelines in 2011 and 2013 and the correlation between overuse of endoscopic surveillance in 2011 and the process indicators associated with the endoscopic workload in 2013. Results: 49 704 postcolonoscopy recommendations were analysed. High-risk, intermediate-risk and low-risk adenomas, and no adenomas were reported in 5.9%, 19.3%, 15.3% and 51.5% of the cases, respectively. Endoscopic surveillance was inappropriately recommended in 67.4% and 7%, respectively, of cases with low-risk and no adenoma. Overall, 37% of all endoscopic surveillance recommendations were inappropriate (6696/17 860). Overuse of endoscopic surveillance was positively correlated with the extension of invitations (correlation coefficient (cc) 0.29; p value 0.03) and with compliance with post-FIT+ colonoscopy (cc 0.25; p value 0.05), while it was negatively correlated with total colonoscopy waiting times longer than 60 days (cc −0.26; p value 0.05). Conclusions: In organised screening programmes, a high rate of inappropriate recommendations for patients with low risk or no adenomas occurs, affecting the demand for endoscopic surveillance by a third.